Implementation and validation open source code CFD software for the convection heat transfer - Kittipos Loksupapaiboon (2018)
© 2016 ACM. The open source code software (OpenFOAM) was applied to simulate the convection heat transfer between the fresh air flow and a hot tube. The k - ϵ turbulence model was implemented to simulate the convection flow. The SIMPLE algorithm and Upwind method were used to solve the governing equations of the cross flow past a hot tube. Particularly, the computational fluid dynamics (CFD) results were compared with the experimental data of heat transfer by using the P3210 heat transfer bench of Cussons technology. The velocity of fresh air had been adjusted to vary between 5 and 20 m/s meanwhile the heat tube was improved to control temperature between 100 and 200 °C. The comparison between CFD model and physical experiments was in good agreement. The average error of CFD model obtained 4.12 % when compared with experimental data.